Wnt5A/Ryk signaling critically affects barrier function in human vascular endothelial cells. Issue 1 (2nd January 2017) - Skaria, Tom; Bachli, Esther; Schoedon, Gabriele
ABSTRACT: Satisfactory therapeutic strategies for septic shock are still missing. Previously we found elevated levels of Wnt5A in patients with severe sepsis and septic shock. Wnt5A is released by activated macrophages but knowledge of its effects in the vascular system remains scant. Here we investigate the response of human coronary artery endothelial cells (HCAEC) to Wnt5A. We used a genome-wide differential expression approach to define novel targets regulated by Wnt5A. Gene ontology analysis of expression profiles revealed clusters of genes involved in actin cytoskeleton remodeling as the predominant targets of Wnt5A. Wnt5A targeted Rho-associated protein serine/threonine kinase (ROCK), leading to phosphorylation of LIM kinase-2 (LIMK2) and inactivation of the actin depolymerization factor cofilin-1 (CFL1). Functional experiments recording cytoskeletal rearrangements in living cells showed that Wnt5A enhanced stress fiber formation as a consequence of reduced actin depolymerization. The antagonist Wnt inhibitory factor 1 (WIF1) that specifically interferes with the WIF domain of Ryk receptors prevented actin polymerization. Wnt5A disrupted β-catenin and VE-cadherin adherens junctions forming inter-endothelial gaps. Functional experiments targeting the endothelial monolayer integrity and live recording of trans-endothelial resistance revealed enhanced permeability of Wnt5A-treated HCAEC. Ryk silencing completely prevented Wnt5A-induced endothelial hyperpermeability. Wnt5A decreased wound healing capacity of HCAEC monolayers; this was restored by the ROCK inhibitor Y-27632. Here we show that Wnt5A acts on the vascular endothelium causing enhanced permeability through Ryk interaction and downstream ROCK/LIMK2/CFL1 signaling. Wnt5A/Ryk signaling might provide novel therapeutic strategies to prevent capillary leakage in systemic inflammation and septic shock.